PENGAJARAN BAHASA INGGRIS INOVATIF BAGI GURU DI SD PUAY YOKA KABUPATEN JAYAPURA PAPUA - Monika Gultom (LPPM Uncen, 2017)
Trash The community service activities aims at socialization of English teaching innovative for teachers in elementary school, in Puay, Yoka, Jayapura in order to help the teachers in these schools in developing learning methodologies given increasing quality and thus is expected to have an impact on improving the quality of the quality of learning and quality graduates at the school. The specific objective of community service activities is to introduce teachers to some innovation in English language learning, especially to students at a very young age. Besides community service activities will involve some of the students of English language education III semester that follows the course English for Young Learner (EYL) are taught by the chairman of the operations in which the activity is also one form of the application of science and theory studied in the course. Community service activities will be carried out for approximately one month including the deepening of the material on the innovative English language teaching for students prior to the field survey locations of service activities, the implementation of service activities, and community service activities seminars results. Community service activities is useful for the improvement / updating knowledge of English teachers in elementary Puay Yoka Jayapura District, field experience is valuable for student teachers of English in the Language Study Program English FKIP UNCEN in applying science and knowledge after attending the course English for Young Learner (EYL) and to know and understand the world of teaching was coming later after completion of study, and is also beneficial for the introduction and promotion of Language Study Program English FKIP UNCEN for students in elementary Puay Yoka Jayapura district which is a prospective student potential future. Keywords: Teaching, English, Innovative